2019
DOI: 10.1002/rcr2.478
|View full text |Cite
|
Sign up to set email alerts
|

Erratic coil migration in the bronchus after bronchial artery embolization

Abstract: Herein, we report two cases of erratic coil migration from the bronchial artery to the bronchus after bronchial artery embolization (BAE). Neither patient exhibited haemoptysis recurrence, but chest radiographs revealed that part of the coil had disappeared. In Case 1, the patient coughed up the coil 4.5 years after BAE. We performed repeat BAE to minimize the possibility of haemoptysis considering bronchoscopic and angiographic findings. In Case 2, the patient had severe dry cough 2 years after BAE. Chest rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Although embolization is 80-90% effective at controlling acute hemoptysis from all causes, the three-year recurrence of hemoptysis is nearly 45% [10]. Complications of coil implantation such as erosion and migration have been reported years after intervention, and migration into the airway is uncommon but has been described [11][12][13]. A literature review in 2013 evaluated 107 reports of PAA treatment in patients with BD and evaluated medical, endovascular, and surgical management in a total of 173 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although embolization is 80-90% effective at controlling acute hemoptysis from all causes, the three-year recurrence of hemoptysis is nearly 45% [10]. Complications of coil implantation such as erosion and migration have been reported years after intervention, and migration into the airway is uncommon but has been described [11][12][13]. A literature review in 2013 evaluated 107 reports of PAA treatment in patients with BD and evaluated medical, endovascular, and surgical management in a total of 173 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since the coil was placed in the vessel, fistula formation by coil migration may induce fatal massive hemoptysis [ 12 ], air embolism [ 13 ] or retrograde infection to the blood stream. It has also been reported that the metallic coil as a foreign body induced cough and hoarseness [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a previous report on bronchoscopic removal of migrated coil after bronchial artery embolization. The authors carefully split the coil by a loop cutter and removed by forceps [ 14 ]. We did not choose transbronchial coil removal under intubation because of the possibility of massive hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a low rate of complications, coil embolization for pulmonary artery disorders do pose some risks such as recanalization, coil migration, coils misplaced in undesirable sites, damage to the vessel wall and delayed bacterial contamination of the thrombus and pulmonary artery. Erratic coil migration into the bronchial tree or other areas of the lung parenchyma is a very rare complication, with only a few cases having been described in the literature [ 3 5 ]. Erosion into the bronchi results in cough, expectoration, haemoptysis, and hoarseness [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Erratic coil migration into the bronchial tree or other areas of the lung parenchyma is a very rare complication, with only a few cases having been described in the literature [ 3 5 ]. Erosion into the bronchi results in cough, expectoration, haemoptysis, and hoarseness [ 3 ]. The fistulisation into the pulmonary artery can result in air embolism or life-threatening haemoptysis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%